Peatland Biodiversity Learning through Virtual Reality: a Case Study at Muhammadiyah Palangka Raya University - Rosdiani, Feni; Dewi, Kurnia; Senopi; Murni; Yutiva, Melan; Imelda; Zannah, Fathul; Syahbana, Rezky Aulianur (Bioilmi: Jurnal Pendidikan, 2025)
Tropical peatland ecosystems are ecologically important yet often neglected in formal biology education due to accessibility and logistical limitations. In Central Kalimantan, where peatland biodiversity is rich but difficult to observe directly, students face challenges in understanding complex ecological interactions and local environmental issues. This study examined the effectiveness of Virtual Reality (VR) as an immersive learning tool to enhance students’ conceptual understanding, engagement, and ecological awareness. A mixed-methods exploratory-descriptive design was employed involving 14 undergraduate students from the Biology Education program at Universitas Muhammadiyah Palangka Raya. Participants interacted with a custom-developed VR module titled “Exploring Peatland Biodiversity” during two guided sessions over two weeks. Data were collected through pre- and post-tests, observation checklists, and focus group discussions (FGDs). Results showed a significant increase in students’ learning outcomes, with average test scores rising from 56.93 (pre-test) to 81.79 (post-test). A paired samples t-test confirmed the improvement as statistically significant (mean difference = 24.86, p < 0.001). Qualitative findings revealed that students perceived the VR module as realistic and emotionally engaging. They demonstrated improved species recognition, understanding of ecological processes, and awareness of threats such as deforestation and peat fires. The study concludes that VR offers an effective solution for biodiversity learning in remote and fragile ecosystems, enhancing both knowledge and environmental concern.